Design and development of sensor based traffic light system - Albagul, Abdulgani; Hrairi, Meftah; Wahyudi, Martono; Hidayathullah, M. F. (Science Publications, 2006)
The main object of this study was to design and implement a suitable algorithm and its simulation for an intelligent traffic signal simulator. The system developed is able to sense the presence or absence of vehicles within certain range by setting the appropriate duration for the traffic signals to react accordingly. By employing mathematical functions to calculate the appropriate timing for the green signal to illuminate, the system can help to solve the problem of traffic congestion. The simulation of the algorithm of the traffic signal system was done using MATLAB software. Hardware simulation tests were successfully performed on the algorithm implemented into a controller. The new timing scheme that was implemented promises an improvement in the current traffic light system and this system is feasible, affordable and ready to be implemented especially during peak hours. A countdown timer interfacing according to the traffic system using Lab VIEW software was also created.